Trailing-edge noise reduction of a wing by a surface modification - Varun Bharadwaj Ananthan and Rinie A. D. Akkermans and Dragan Kozulovic (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2021)
There is an increased emphasis on reducing airframe noise in the last decades. Airframe noise is sound generated by the interaction of a turbulent flow with the aircraft geometry, and significantly contributes to the overall noise production during the landing phase. One examples of airframe noise is the noise generated at a wing's trailing edge, i.e., trailing-edge noise. In this contribution, we numerically explore the local application of riblets for the purpose of trailing-edge noise reduction. Two configurations are studied: i) a clean NACA0012 wing section as a reference, and ii) the same configuration with riblets installed at the wing's aft part. The numerical investigation follows a hybrid computational aeroacoustics approach, where the time-average flow is studied by means of RANS. Noise sources are generated by means of a stochastic approach called Fast Random Particle Mesh method. The results show a deceleration of the flow behind the riblets. Furthermore, the turbulent kinetic energy indicates increased unsteadiness behind the riblets which is shifted away from the wall due to the presence of the riblets. Lastly, the sound sources are investigated by means of the 3D Lamb-vector, which indicates a slight reduction in magnitude near the trailing edge.